Foreign institutional ownership and the speed of leverage adjustment: International evidence - An, Zhe; Chen, Chen; Li, Donghui; Yin, Chao (Journal of Corporate Finance, 2021)
Employing a large sample of 7246 firms across 38 economies from 2000 to 2013, we show a positive relation between foreign institutional ownership (FIO) and firms' speed of leverage adjustment. This positive relation is concentrated for over-leveraged firms that need to decrease financial leverage to rebalance their capital structures. We validate our findings using a 2SLS regression and a DiD estimation to exploit the exogenous variations in FIO generated by the inclusion of MSCI membership and the passage of the JGTRRA. These results suggest that foreign institutional investors play an important monitoring role in mitigating agency conflicts between shareholders and managers. Overall, this paper lends support to the dynamic trade-off theory.